2012
DOI: 10.1111/j.1744-9987.2012.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Level of C‐Reactive Protein in Chronic Hemodialysis Patients: A Comparative Study Between Patients With Non‐Infected Catheters and Arteriovenous Fistula in a Large Saudi Hemodialysis Center

Abstract: Central venous catheters are associated with infection and resultant higher C-reactive protein levels (CRP), suggesting that catheters may be an important determinant of increased inflammatory response. The increased levels of markers such as CRP are associated with increased risk of premature death and hospitalization in end stage renal disease (ESRD) patients on regular hemodialysis (HD). In this prospective study the mean levels of the inflammatory marker CRP were measured every 2 months over a period of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Although inflammation etiology in patients undergoing hemodialysis is varied (15), they put on show the highest level of inflammation likely due to hidden infection associated with arteriovenous fistula or central venous catheters (16), confrontation with endotoxin, and other pollutants and bioincompatible dialysis solution and membrane (17). …”
Section: Introductionmentioning
confidence: 99%
“…Although inflammation etiology in patients undergoing hemodialysis is varied (15), they put on show the highest level of inflammation likely due to hidden infection associated with arteriovenous fistula or central venous catheters (16), confrontation with endotoxin, and other pollutants and bioincompatible dialysis solution and membrane (17). …”
Section: Introductionmentioning
confidence: 99%
“…Some authors have demonstrated that, even in the absence of catheter-related infection, patients receiving hemodialysis through a catheter had significantly higher serum concentrations of C-reactive protein, suggesting that chronic inflammation could be the reason for their significantly higher mortality rate (2)(3)(4). However, some patients are unable to have an arteriovenous fistula and it is therefore highly important to identify the mechanism through which catheters trigger a chronic inflammatory response even in the absence of clinically evident infection.…”
mentioning
confidence: 99%
“…Indeed, it has been recognised that the use of CVC locking solutions maintains CVC patency and prevents infections, probably because of the reduction in conditioning biofilms. 28,29 Our study shows the presence of non-bacterial biofilms or conditioning films in all CVCs examined regardless of the type of locking solution used. According to our results, the taurolidine group was associated with significantly lower biofilm thickness and volume than the citrate 4% and heparin groups.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, in recent years, it has been shown that patients with CVCs have a greater inflammatory response (higher serum CRP) than patients with AVF, which has not been explained so far. 29,30 Possibly, the type of locking solution instilled into the CVC could reduce this response. 20 According to the results of previous studies, the presence of adherent biological materials 8 in CVCs could lead to clot formation and CVC dysfunction and become the optimal environment for the attachment of different bacteria or fungi.…”
Section: Discussionmentioning
confidence: 99%